Dynamic Triaxial Test and Microscopic Study of Solidified Muddy Soil With Different Mixing Ratios and Curing Ages - Chen, Zhou; Xu, Haocheng; Cheng, Mayao; Lu, Hanwen; Wang, Zhijian; Feng, Peiyu (Frontiers in Materials, 2021)
Aiming to explore the optimal mixture ratio and curing age of solidified muddy soil under dynamic load, the paper intends to investigate whether the solidified muddy soil can be used as filling of high-speed railway subgrade. Based on the dynamic triaxial test, the investigation measured the dynamic strain and dynamic elastic modulus of solidified muddy soil under different mix ratios and curing ages, and also observed the microscopic morphology of solidified muddy soil samples by using SEM (scanning electron microscope).The results show that the addition of cement and curing agent significantly increases the dynamic strength and elastic modulus of muddy soil, which effectively improve the dynamic characteristics of muddy soil. The curing effect of the curing agent is more obvious with the increase of the dosage of cement and curing agent under different mix ratio. The content of curing agent plays a leading role in the hydration reaction between cement, curing agent and soil particles. Additionally, in case of the same test conditions, when the ratio of cement mass to dry silt mass is 1:20, the ratio of diluent volume to dry silt mass is 1:20, with 28 days of curing age, its curing effect will reach the best.